2019
DOI: 10.1002/adfm.201901761
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable Multifunctional Graphene Oxide Platform for Targeted Cancer Therapy

Abstract: The design of multifunctional materials able to both selectively deliver a drug into cells in a targeted manner and display an enhanced propensity for biodegradation is an important goal. Here, graphene oxide (GO) is functionalized with the chemotactic peptide N-formyl-methionyl-leucylphenylalanine (fMLP) known to interact with the formyl peptide receptor, which is expressed in different cancer cells, including cervical carcinoma cells. This study highlights the ability of GOfMLP for targeted drug delivery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…3 Furthermore, we demonstrated in a previous study that primary human neutrophils are capable of degrading GO when activated to undergo degranulation with release of MPO, 4 while GO functionalized with a chemotactic peptide triggered neutrophil activation with subsequent degradation of GO. 5 Single-and few-layer graphene is also susceptible to enzymatic degradation though the process was found to be less efficient as compared to GO. 6 Previous studies on single-and multi-walled carbon nanotubes (CNTs) have revealed the propensity of these materials to undergo peroxidase-mediated biodegradation.…”
mentioning
confidence: 99%
“…3 Furthermore, we demonstrated in a previous study that primary human neutrophils are capable of degrading GO when activated to undergo degranulation with release of MPO, 4 while GO functionalized with a chemotactic peptide triggered neutrophil activation with subsequent degradation of GO. 5 Single-and few-layer graphene is also susceptible to enzymatic degradation though the process was found to be less efficient as compared to GO. 6 Previous studies on single-and multi-walled carbon nanotubes (CNTs) have revealed the propensity of these materials to undergo peroxidase-mediated biodegradation.…”
mentioning
confidence: 99%
“…To obtain human monocyte-derived macrophages (HMDMs), CD14 + monocytes were cultured in RPMI-1640 cell medium supplemented with 2mM l-glutamine, 100 IU/ml penicillin, 100 μg/ml streptomycin and 10% heat-inactivated FBS, supplemented with 50 ng/ml recombinant macrophage colony-stimulating factor (M-CSF) (R&D Systems, MN, USA) for 3 days. Peripheral blood neutrophils (PMNs) were isolated from buffy coats as previously described [29]. Briefly, neutrophils were isolated by density gradient centrifugation using Lymphoprep™ followed by gradient sedimentation in a 5% dextran solution and hypotonic lysis of residual erythrocytes.…”
Section: Isolation Of Primary Human Immune Cellsmentioning
confidence: 99%
“…Freshly isolated HMDMs and PMNs were seeded in 96-well plates in phenol red-free RPMI-1640 cell medium at a density of 10 6 cells/ml and exposed to CNPs at the indicated concentrations or were maintained in cell medium alone (negative control). The alamarBlue™ assay (Thermo Scientific, Göteborg, Sweden) was performed for cytotoxicity assessment of the PMNs and HMDMs as described previously [29]. Briefly, following exposure to CNPs, a 10% (v/v) solution of alamarBlue reagent was added to each well.…”
Section: Cytotoxicity Assessment In Primary Cells Alamarblue Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, graphene and its derivatives have been widely studied in the fields of medicine and gene delivery, bioimaging, biodetection, immune‐modulation and cancer treatment . As an emerging member in the graphene family, structurally well‐defined graphene nanoribbons (GNRs) have attracted enormous attention due to their controllable structures including length, width and edges .…”
Section: Figurementioning
confidence: 99%